Impact of DNA methylation on plant growth and development: a study on a methylation-defective mutant of Arabidopsis thaliana - Forgione, Ivano; Bruno, Leonardo; Van Lijsebettens, Mieke (My University, 2017)
Epigenetic modifications of DNA contribute to chromatin remodeling process and gene expression regulation playing a relevant role on the development of eukaryotic organisms. DNA methylation is an important epigenetic mark consisting in the addition of a methyl group on cytosine bases, which is observed in most of the organisms at the different evolution levels. In plants, DNA methylation is controlled by several genetic pathways, encoding different methyltransferases which act on different sequence contexts. Targets for cytosine DNA methylation in plant genomes are CG, CHG and CHH (H is A, T, C) sequences. The plant DNMT1-homolog METHYLTRANSFERASE1 (MET1) maintains DNA methylation at CG sites, whereas the DNMT3 homolog DOMAINS REARRANGED METHYLASE 1 and 2 (DRM1 and DRM2) are responsible for the de novo methylation in all sequence contexts. In addition, the plant-specific CHROMOMETHYLASE3 (CMT3) is responsible for DNA maintenance methylation at CHG sites, as well as at a subset of CHH sites. In plants DNA methylation is involved in diverse biological processes. Loss of methylation in the Arabidopsis thaliana mutants met1 and ddm1 (decrease in DNA methylation 1) causes several developmental abnormalities. Similarly, combined mutations in the DRMs and CMT3 genes induce pleiotropic defects in plants. Here, we used the Arabidopsis thaliana triple mutant drm1 drm2 cmt3, defective in DNA methylation to get deeper insight into the correlation between DNA methylation and plant growth. We identified novel developmental defects of the triple mutant dealing with the agravitropic response of the root and an altered differentiation pattern of the leaf which also exhibits a curly shape. Confocal microscopy of mutant transgenic lines expressing DR5:GFP reporter gene allowed us to verify that the loss of DNA methylation impacts on the accumulation and distribution of auxin from embryo to adult plant. The expression of auxin-related genes has been also found to be altered in drm1 drm2 cmt3 mutant. Furthermore, through an optimized and implemented protocol of comparative analysis of genomic methylated regions based on MeDIP-qPCR, we provide evidence about the direct and organ-specific modulation of auxin-related genes through DNA methylation process. The epigenetic mechanisms interplay with each other rather than work independently to modulate gene function. Accordingly, in our study we provide a novel evidence of the crosstalk between DNA methylation status and histone modification. Indeed, in the drm1 drm2 cmt3 mutant the overexpression of CLF gene, a component of PCR2 complex that performs trimethylation of histone H3 lysine 27, was accompanied by a high level of histone methylation, as evaluated through ChIP-qPCR analysis, and by a concomitant down-regulation of genes target of PRC2 complex action. Thus, the results obtained in these three years of PhD course are encouraging and may open new perspectives in the study of the DNA methylation in plants.
Dottorato di Ricerca in Scienze della Vita. Ciclo XXIX
Keywords: Arabidopsis thaliana; DNA